Economic Development, Economic Problems, and Suicide in Thailand: Empirical Evidence Based on Provincial Data - Charnsarn, Supachet (Animo Repository, 2017)
This study aims to examine the situation and trend of suicide in 76 provinces in Thailand during 2006–2013 and also to investigate the relationship among suicide, economic development, and economic problems by utilizing the feasible generalized least square (FGLS) regression analysis. The findings reveal that the average suicide rate in Thailand during the study period was 5.98 per 100,000 populations and exhibited a slight upward trend. Moreover, Lamphun province had the highest average suicide rate while Pattani province had the lowest rate. Gross provincial product per capita is found to have a curvilinear relationship with total, male, and female suicide rate. That is, suicide rate is likely to decrease as gross provincial product per capita increases but only up to a certain point, thereafter as gross provincial product continues to increase, suicide rate is likely to increase. Additionally, the findings reveal that industrialization and unemployment have the negative effect on suicide rate. In terms of other factors, divorce, having diabetes, and having high blood pressure significantly determine total, male, and female suicide, whereas urbanization affects only male suicide and educational attainment affects only female suicide.